Vibrio parahaemolyticus Senses Intracellular K+ To Translocate Type III Secretion System 2 Effectors Effectively - Sarunporn Tandhavanant; Shigeaki Matsuda; Hirotaka Hiyoshi; Tetsuya Iida; Toshio Kodama (mBio, 2018)
ABSTRACT Many Gram-negative bacterial symbionts and pathogens employ a type III secretion system (T3SS) to live in contact with eukaryotic cells. Because T3SSs inject bacterial proteins (effectors) directly into host cells, the switching of secretory substrates between translocators and effectors in response to host cell attachment is a crucial step for the effective delivery of effectors. Here, we show that the protein secretion switch of Vibrio parahaemolyticus T3SS2, which is a main contributor to the enteropathogenicity of a food poisoning bacterium, is regulated by two gatekeeper proteins, VgpA and VgpB. In the absence of these gatekeepers, effector secretion was activated, but translocator secretion was abolished, causing the loss of virulence. We found that the K+ concentration, which is high inside the host cell but low outside, is a key factor for VgpA- and VgpB-mediated secretion switching. Exposure of wild-type bacteria to K+ ions provoked both gatekeeper and effector secretions but reduced the level of secretion of translocators. The secretion protein profile of wild-type bacteria cultured with 0.1 M KCl was similar to that of gatekeeper mutants. Furthermore, depletion of K+ ions in host cells diminished the efficiency of T3SS2 effector translocation. Thus, T3SS2 senses the high intracellular concentration of K+ of the host cell so that T3SS2 effectors can be effectively injected. IMPORTANCE The pathogenesis of many Gram-negative bacterial pathogens arises from a type III secretion system (T3SS), whereby bacterial proteins (effectors) are directly injected into host cells. The injected effectors then modify host cell functions. For effective delivery of effector proteins, bacteria need to both recognize host cell attachment and switch the type of secreted proteins. Here, we identified gatekeeper proteins that play important roles in a T3SS2 secretion switch of Vibrio parahaemolyticus, a causative agent of food-borne gastroenteritis. We also found that K+, which is present in high concentrations inside the host cell but in low concentrations outside, is a key factor for the secretion switch. Thus, V. parahaemolyticus senses the high intracellular K+ concentration, triggering the effective injection of effectors.